2011
DOI: 10.1074/jbc.m110.205146
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Jarid2/Jumonji Is Required for Normal Cardiac Development and Proper Notch1 Expression

Abstract: Jarid2/Jumonji critically regulates developmental processes including cardiovascular development. Jarid2 knock-out mice exhibit cardiac defects including hypertrabeculation with noncompaction of the ventricular wall. However, molecular mechanisms underlying Jarid2-mediated cardiac development remain unknown. To determine the cardiac lineagespecific roles of Jarid2, we generated myocardial, epicardial, cardiac neural crest, or endothelial conditional Jarid2 knockout mice using Cre-loxP technology. Only mice wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
78
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 77 publications
(83 reference statements)
6
78
0
Order By: Relevance
“…Our findings suggest that Fkbp1a has a role in regulating endocardial Notch1 activity, which is crucial to ventricular wall formation. Our findings are entirely consistent with recent reports by Mysliwiec and colleagues that upregulation of Notch1 in endocardial cells leads to ventricular hypertrabeculation and noncompaction (Mysliwiec et al, 2011;Mysliwiec et al, 2012). Most recently, Yang and colleagues demonstrated that upregulated Notch2 activity in Numb/Numb-like compound deficient mutants contributes to Bmp10 upregulation and ventricular hypertrabeculation and noncompaction phenotypes (Yang et al, 2012), further validating our conclusion.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings suggest that Fkbp1a has a role in regulating endocardial Notch1 activity, which is crucial to ventricular wall formation. Our findings are entirely consistent with recent reports by Mysliwiec and colleagues that upregulation of Notch1 in endocardial cells leads to ventricular hypertrabeculation and noncompaction (Mysliwiec et al, 2011;Mysliwiec et al, 2012). Most recently, Yang and colleagues demonstrated that upregulated Notch2 activity in Numb/Numb-like compound deficient mutants contributes to Bmp10 upregulation and ventricular hypertrabeculation and noncompaction phenotypes (Yang et al, 2012), further validating our conclusion.…”
Section: Discussionsupporting
confidence: 82%
“…46 Also in the developing myocardium, endothelial deletion of Jarid2, a member of the Jumonji family of proteins that is not active as a demethylase but associates with the PcG complex to modulate its function, 47,48 derepresses endocardial Notch1 expression. 49 In addition, deletion of Ezh2 in cardiac progenitors is known to cause postnatal myocardial pathology. 50 In neonatal cardiomyocytes, chromatin-mediated suppression of the Notch target genes was effectively counteracted by the forced activation of the Notch pathway on AAV-mediated gene transfer.…”
Section: Discussionmentioning
confidence: 99%
“…8 For JARID2, an important role of endocardial-driven cardiac development has been reported. 9,10 The function of the other JARID enzymes in the cardiovascular system has not been studied. In this study, we found the enzyme JARID1B, which has been implicated in cell fate decision, cancer progression, and stem cell self-renewal, 5,[11][12][13] to be highly expressed in ECs.…”
mentioning
confidence: 99%